Concussion history and virtual reality metrics predict core or lower extremity injury occurrence among high school athletes - Wilkerson, Gary B.; Wynn, Kimberly R.; Dill, Paige W.; Acocello, Shellie; Carlson, Lynette M.; Hogg, Jennifer (Frontiers in Sports and Active Living, 2024)
A history of concussion is recognized as a risk factor for musculoskeletal injury, which is likely associated with physiological effects that need to be better understood. The purpose of this study was to assess the potential for measurements derived from an immersive virtual reality test to identify a subtle perceptual-motor impairment that may be prospectively associated with the occurrence of a core or lower extremity sprain or strain. A cohort of 68 high school athletes (41 female soccer players and 27 male football players) provided survey responses and completed an immersive virtual reality test several days prior to initiation of pre-season practice sessions. Measurements of eye, neck, arm, and whole-body displacements were acquired during 40 successive lunging/reaching responses to visual stimuli that moved horizontally across the virtual reality headset display. Injury occurrences were electronically documented from the first pre-season practice session to the final game of the season. A statistically significant and intrinsically credible 2-factor prediction model for core or lower extremity injury occurrence included an interaction between female sex and a self-reported history of 2 or more concussions, along with slow response time for arm reach (OR = 4.67; 95% CI, 1.51-14.43). Follow-up analyses identified sex-specific cut points for arm reach response time associated with elevated injury risk, which were ≥ 1.385 s for females and ≥ 1.257 s for males. High school female soccer players who have sustained more than one concussion appear to be highly vulnerable to core or lower extremity sprain or strain, with injury risk compounded by slow arm reach response time. Male football players as a group demonstrated significantly faster arm reach response time than female soccer players, but slow perceptual-motor response time for arm reach was also identified as a potentially important injury risk factor for males. Immersive virtual reality appears to provide precise measurements of behavioral performance characteristics that depend on brain processing efficiency. Because the speed, accuracy, and consistency of perceptual-motor responses may be modifiable, future research should assess the potential benefit of virtual reality training for reduction of sport-related injury risk.